Insights into the cellular pathophysiology of familial hemophagocytic lymphohistiocytosis - Steen, Erica A.; Nichols, Kim E.; Meyer, Lauren K. (Frontiers in Immunology, 2023)
Familial hemophagocytic lymphohistiocytosis (fHLH) encompasses a group of rare inherited immune dysregulation disorders characterized by loss-of-function mutations in one of several genes involved in the assembly, exocytosis, and function of cytotoxic granules within CD8+ T cells and natural killer (NK) cells. The resulting defect in cytotoxicity allows these cells to be appropriately stimulated in response to an antigenic trigger, and also impairs their ability to effectively mediate and terminate the immune response. Consequently, there is sustained lymphocyte activation, resulting in the secretion of excessive amounts of pro-inflammatory cytokines that further activate other cells of the innate and adaptive immune systems. Together, these activated cells and pro-inflammatory cytokines mediate tissue damage that leads to multi-organ failure in the absence of treatment aimed at controlling hyperinflammation. In this article, we review these mechanisms of hyperinflammation in fHLH at the cellular level, focusing primarily on studies performed in murine models of fHLH that have provided insight into how defects in the lymphocyte cytotoxicity pathway mediate rampant and sustained immune dysregulation.